ANALISA TRANSPORTASI PALM OIL MILL EFFLUENT DARI PABRIK KELAPA SAWIT KE PEMBANGKIT LISTRIK TENAGA BIOGAS DI RIAU - Ardhi wahyu Eka; Hasan Iqbal Nur; Khumaidah Nur (ROTOR, 2017)
The delivery of Palm Oil Mill Effluent (POME) by the Palm Oil Mill (POM) of Tanah Putih (60,000 tons / year) and POM Sei Buatan (30,000 tons / year) through the river ship represents 78% of POME's total supply requirement for Biogas Power Plant (BPP) Tandun, Riau. How to get recommendations on routes, ship types and most optimum ship sizes is important. The optimization is done by analyzing the transportation including the investment and then comparison between the modes with some alternative routes on the existing segment, the actual condition limitation and the minimum criterion of total cost. The result of analysis shows that for POME delivery the optimum route is port to port using 1 unit of SPOB vessel with 1,500 ton capacity for each segment. The optimum ship type is Self Propelled Oil Barge (SPOB) when compared to Self Propelled Container Barge (SPCB) and Landing Craft Tank (LCT) and Tank Truck with 8 ton capacity. The total cost for ship procurement is Rp 8,035 billion. The amount of POME delivered can generate 9 million kWh of electrical power. Total revenues from electricity sales and electricity cost savings of the factory amounted to Rp 8.774 billion, resulting in a gross profit of Rp 739 million Keywords: Transportation Analysis, Palm Oil Mill Effluent, Biogas Power Plant